1998
DOI: 10.1093/emboj/17.5.1446
|View full text |Cite
|
Sign up to set email alerts
|

An embryonic demethylation mechanism involving binding of transcription factors to replicating DNA

Abstract: In vertebrates, transcriptionally active promoters are undermethylated. Since the transcription factor Sp1, and more recently NF-κB, have been implicated in the demethylation process, we examined the effect of transcription factors on demethylation by injecting in vitro methylated plasmid DNA into Xenopus fertilized eggs. We found that various transactivation domains, including a strong acidic activation domain from the viral protein VP16, can enhance demethylation of a promoter region when fused to a DNA bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 57 publications
(73 reference statements)
7
66
1
1
Order By: Relevance
“…While mechanisms of site-specific demethylation are poorly understood, recent studies suggested that protein binding to a certain DNA sequence during DNA replication specifies sites of DNA demethylation by inhibiting remethylation of the replicated strand. [24][25][26] Therefore, it is conceivable that certain sequences in the 3 0 UTR play critical roles in the site-specific demethylation and SDF1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…While mechanisms of site-specific demethylation are poorly understood, recent studies suggested that protein binding to a certain DNA sequence during DNA replication specifies sites of DNA demethylation by inhibiting remethylation of the replicated strand. [24][25][26] Therefore, it is conceivable that certain sequences in the 3 0 UTR play critical roles in the site-specific demethylation and SDF1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly show that the PE element is not only a transcriptional enhancer but it is also a cis-demodification element that demethylates/protects the DNA in a cell-and stage-specific manner. The observation that enhancer sequences are part of several identified demodification elements (20, 27, 44 -46) and the fact that demethylation does not seem to occur as a consequence of transcriptional activation (47)(48)(49) strongly suggest that enhancers may have two separate and independent functions, first to target genes for epigenetic modification and second to stimulate RNA synthesis.…”
Section: Fig 6 Methylation Repressesmentioning
confidence: 99%
“…It has been nearly 40 y since it was suggested that genomic methylation patterns could be transmitted via maintenance methylation during S phase and might play a role in the dynamic regulation of gene expression during development [Holliday R, Pugh JE (1975) Science 187(4173):226-232; Riggs AD (1975) Cytogenet Cell Genet 14(1): [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This revolutionary proposal was justified by "... our almost complete ignorance of the mechanism for the unfolding of the genetic program during development" that prevailed at the time.…”
mentioning
confidence: 99%